Relationship between preoperative hospital stay and the occurrence of SSI in clean orthopedic surgeries in a public teaching hospital in the Federal District. - Rodrigues Mangueira, Nayara (2025)
Objective: to analyze whether the preoperative length of stay of all patients who underwent clean orthopedic surgeries in a public teaching hospital in the Distrito Federal in the first half of 2020 had an impact on the incidence of SSI in these patients. Method: retrospective, descriptive, exploratory and quantitativestudy to be conducted from secondary data in the records of the Hospital Infection Control Center (NCIH) and information extracted via electronic medical records (TrackCare®), with a simple percentage analysis from of the Excel program. Results:the study population consisted of 76 patients, 75% (57) were male and 25% (19) were female. As for the patients who presented SSI, 9.2% (7) had a mean preoperative hospital stay of 9.7 days. Patients who did not develop SSI had exactly the same mean number of days. Conclusion: the study presented suggests that there is no graphic relevance between the preoperative time in the occurrence of SSI in isolation, since the average (9.7 days) was the same for patients who infected and for those who did not. There should be a new study with the time period and a larger sample for better statistical analysis.